Forming Team Synergy: Conflict Management in MSMEs - titan, moh. maryndo; Soeprijatno, Edy Djoko (Universitas Nusantara PGRI Kediri, 2025)
Research objectives: This study aims to explore the application of conflict management in creating team synergy in Wholesale Pillow Kediri, as well as understand the factors that affect team dynamics Design/Method/Approach: This study uses a qualitative approach with in-depth interviews and participatory observation as a data collection method. The informants involved are employees and owners at Kediri Pillow Wholesale MSMEs. Research Findings: The results show that the implementation of effective conflict management, such as open communication and mediation, contributes significantly to improving team synergy. There are several strategies that have been successfully implemented, including team training and the preparation of internal regulations to handle conflicts. Theoretical contribution/originality: This research provides new insights into the importance of conflict management in the context of local businesses, especially in the MSME sector. These findings add to the literature on team management and conflict dynamics in the work environment. Practitioner/Policy Implications: This study recommends the implementation of more structured conflict management strategies in small and medium-sized companies to improve team performance and achieve common goals. Limitations of the study: The limitations of this study are the focus on a single location and the lack of generalization of the results. Further research is suggested to cover more locations and industry variations.